Media Komunikasi Pemasaran Usaha Jamu Buk Tum Didesa Andongsari Kecamatan Ambulu - Rizqi, Lika (Program Studi Ilmu Komunikasi, 2023)
Technological civilization is developing very quickly with many advances in the economic, political, socio-cultural and educational fields. In the field of marketing, communication is very much needed to market products and services. Current technological capabilities answer all challenges on how to market products and services more effectively and efficiently. Increasingly developing technology makes communication possible using communication media. Communication is carried out using communication media, namely WhatsApp. Whatsapp is a cross-platform messaging application that allows us to exchange voice and text messages without using credit, because WhatsApp uses the internet or wifi network. The title of this research is